1995
DOI: 10.1136/adc.73.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Infantile osteopetrosis; bone marrow transplantation from a cousin donor.

Abstract: [453][454][455]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…17,18 The role of BMT for osteopetrosis secondary to CAII deficiency, a condition that may have very significant morbidity but an ill-defined mortality risk, has not been previously described. We have demonstrated that BMT does benefit these patients because it reversed osteopetrosis and, in doing so, stabilized vision and hearing and improved their growth potential.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The role of BMT for osteopetrosis secondary to CAII deficiency, a condition that may have very significant morbidity but an ill-defined mortality risk, has not been previously described. We have demonstrated that BMT does benefit these patients because it reversed osteopetrosis and, in doing so, stabilized vision and hearing and improved their growth potential.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to immune recovery, bone remodeling, improved growth and survival. [5][6][7][8][9][10][11][12] In this study we report the outcomes of 10 patients with infantile osteopetrosis, transplanted at the University of Minnesota between 1978 and 1997. The data indicate that allogeneic HCT can be an effective therapeutic option for these children.…”
mentioning
confidence: 99%